Integrating benthic ecological status and spatial planning to guide sustainable bottom-contacting fisheries in the Eastern Mediterranean - Irini Tsikopoulou; Irida Maina; Nadia Papadopoulou; François Bastardie; Chris J. Smith (Frontiers in Marine Science, 2026)
To inform ecosystem-based fisheries management in line with the EU legislation objectives for marine fisheries, we evaluated the ecological outcomes of alternative spatial management scenarios to fisheries that consider the ecological impact of bottom trawling on the benthic ecosystem in the Eastern Ionian Sea. Trawling intensity in terms of swept area ratio (SAR) and benthic community sensitivity were combined to estimate the relative benthic status (RBS). Then, five management scenarios were tested. The scenarios include four static closure scenarios (below 800 m, below 600 m, the least-trawled 10% of fishing grounds, and areas shallower than 150 m), where trawling is completely excluded without fishing effort redistribution, and one with a trawl ban in all marine protected areas, where fishing effort displacement is modelled dynamically. Baseline RBS was high (>0.9 on a scale of 0 to 1 where 1 is unaffected benthic community) in all habitats, reflecting relatively low benthic degradation due to bottom trawling. Excluding bottom trawling from areas shallower than 150 m in depth produced the greatest improvements, while thresholds at 600 or 800 m depth, and the closure of the 10% least-trawled grounds, had no significant effects on benthic ecological status. Closure of trawling in the marine protected areas produced mixed outcomes, with improvements in some habitats but localized declines due to displaced effort in others. Our study demonstrates the value of including benthic indicators in spatial management strategies to guide adaptive, evidence-based fisheries governance, balancing conservation objectives with socio-economic sustainability.